INNOVATIVE TEACHING STRATEGIES FOR TEACHING READING: RECIPROCAL TEACHING STRATEGY AND FACE STORY STRATEGY - Santi Oktarina, Putu (Institut Hindu Dharma Negeri Denpasar, 2018)
The main task in reading is to develop students' reading skills. This means motivating them to read. Real readers do something with what they read. Actually, students think that reading is an important thing to do. Because by reading they can achieve important goals or answer the questions they want. So, they are motivated to read because while reading they empower or enrich their knowledge. As teachers, we believe when we say